(untitled) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
This bibliography includes articles, studies and books that are dedicated to an important figure of the fifteenth-century Serbian culture – a ruler and writer Helen Balšić. The novels, plays and other non-scientific writings dealing with her life are also listed. Editions of her works – letters, contract with Venice, ktitor inscription and testament – are noted as well. Even the texts in which she is only mentioned are taken into account. The order is chronological.